Incidental detection of two adult gravid filarial worms in breast: a case report - Santosh Tummidi; Kanchan Kothari; Roshni Patil; Shruti S. Singhal; Pooja Keshan (BMC Research Notes, 2017)
Abstract Background Microfilaria is a major public health problem in tropical and subtropical countries and is an endemic problem in India. Wuchereria bancrofti is the commonest filarial infection. In some lesions, microfilariae and adult filarial worm have been incidentally detected in fine-needle aspirates. Case presentation A 35 year old hindu female presented with lump in upper outer quadrant of left breast. Fine needle aspiration revealed two adult gravid female filarial worms. Conclusion To our knowledge this is the first ever case report to demonstrate two live gravid female and embryoid forms in wet mount preparation.